Alternative International Relations Perspective: The Case of Humanitarian Intervention - David Willis; Aryanta Nugraha (Jurusan Ilmu Hubungan Internasional, 2015)
This article examines three alternative International Relations theories, the English School, both its pluralist and solidarist forms, Marxism and postcolonialsm, and their insights and approaches toward the modern international phenomenon of humanitarian intervention. In particular, it identifies the key analytical tools used by each to understand, explain, and interpret said phenomenon, namely, international society and two separate notions of imperialism. Martin Wight’s famous typology of the three traditions of International Relations: Rationalism, Realism and Revolutionism is used to explore the fundamental differences between the theories. Ultimately, the article identifies that the perspectives’ views on humanitarian intervention are broadly: endorsement on the behalf of English School solidarists and ranging from caution to hostility on the behalf of English School pluralists, Marxists and postcolonialists. The authors concludes in favour of limited support for humanitarian intervention in line with that of the English School pluralists.